EKSPLORASI ETNOMATEMATIKA PADA ALAT MUSIK KELENTANGAN MAHANG KHAS BANYUASIN: Ethnomathematics Exploration of the Banyuasin Mahang Kelentangan Musical Instrument - Abdullah, Anisyah; Fitrianti, Yuli (Universitas Tadulako, 2023)
Ethnomatematics is a science that studies mathematical concepts that exist in a particular culture. Culture in Indonesia is very diverse, one of which is traditional musical instruments. Kelentangan Mahang is a traditional musical instrument originating from Banyuasin Regency, South Sumatra Province. The purpose of this study is to explore mathematical concepts and provide an explanation of the length, volume and weight of the blade that affect the sound produced from the loudness of the mahang. The method used in this study is descriptive qualitative method of observation, interviews, and document studies. The results in this study show the ethnomathematics elements of mahang malleability and multiple regression equations as well as the exponential equation of length, diameter, and blade volume data with the frequency obtained. The following equation is generated: The equations found can be used to help craftsmen make Kelentangan Mahang, especially in the sound produced from each of the wooden blades of the musical instrument.